Robotic total station performance in industrial deformation solution - Idris, Khairulnizam M.; Setan, Halim (2006)
Robotic Total Station or Robotic Tachometry System (RTS) widely used for surveying purpose and solution. From surveyor to archeologist, professional used RTS to solve many problems in collecting data such as to mapping the land use, archeology excavation site or used in construction field. Latest technology adopted in modern total station is servo motors to drive both the horizontal and vertical motion of the instruments. This technology designed special to search automatically for prism target known as Automatic Target Recognition (ATR). Manufacturers such as Leica Geosystem, TOPCON Instrument, Trimble and Geodimeter have designed an instrument with automatic target recognition (ATR). This technology utilizes an infrared light bundle sent co-axially through the telescope. Usually, RTS will be used in precise measurement application such as deformation monitoring or dimensional surveying for industrial. Both applications needed high precision instrument and accuracy. This paper presented the developed software system known Industrial Deformation Data Acquisition and Analysis (InDA) using ATR functions of Leica Robotic Total Station. The data has validated by well-known software, Leica APSWin. Developed software can avoid gross error from observer and also systematic error for further analysis. The data from APSWin has analyzes and compared to observation data from InDA.